Understanding the effect of organizational culture and employee engagement on organizational performance using organizational communication as mediator: a conceptual framework - Mary Monica Jiony; Geoffrey Harvey Tanakinjal; Daria Gom; Ruth S. Siganul (Scientific & Academic Publishing, 2015)
This paper attempts to investigate the relationships between employee engagement and organization culture and to explore what drives employee engagement. Engagements at work, organizational communication, organizational culture, and workforce effectiveness have gained much popularity and a considerable amount of discussions among employers and indeed is of escalating interest to researchers. Various research suggested that there is a need to focus on research that holistically cover the most significant issues of the subject and not to always arrive at more or less similar results. Therefore, aiming to fill this gap, this study proposes a conceptual framework to understand the effect of organizational culture on employee engagement and organizational performance. In addition, this study also suggests the adoption of organizational communication as mediator as it is one of the critical factors in producing an ideal environment which cultivates the best out of employees and organizations, and the commitment and experiences of the people in it. First, the concepts of organizational culture, employee engagement, organizational communication and organizational performance are briefly discussed. Then, the proposed conceptual framework for the study is presented. The intended participants of this study are fulltime executive level employees in selected 5star hotels located in Sabah, Malaysia. This study plans to employ a combination of qualitative and quantitative methods in addition to using survey instrument design and Likert Scale questionnaire to assess dimensions of all constructs and the level of engagement of employees. Western studies may provide comparable findings in Asian studies due to certain similarities in the environment, culture, and communications. However, there has, so far, been no consensus in terms of results, thus more in-depth research on this area of employee engagement at work, organizational culture, and communication is required.